Breaking the Fourth Wall: Modulating Quaternary Associations for Protein Regulation and Drug Discovery. (1st April 2019) - Long, Marcus J. C.; Hnedzko, Dziyana; Kim, Bo Kyoung; Aye, Yimon
Abstract: Protein–protein interactions (PPIs) are an effective means to orchestrate intricate biological processes required to sustain life. Approximately 650 000 PPIs underlie the human interactome; thus underscoring its complexity and the manifold signaling outputs altered in response to changes in specific PPIs. This minireview illustrates the growing arsenal of PPI assemblies and offers insights into how these varied PPI regulatory modalities are relevant to customized drug discovery, with a focus on cancer. First, known and emerging PPIs and PPI‐targeted drugs of both natural and synthetic origin are categorized. Building on these discussions, the merits of PPI‐guided therapeutics over traditional drug design are discussed. Finally, a compare‐and‐contrast section for different PPI blockers, with gain‐of‐function PPI interventions, such as PROTACS, is provided. Abstract : Customizable PPIs : Protein–protein interactions (PPIs) are effective at regulating the biological processes required to sustain life. This minireview illustrates the growing arsenal of PPI assemblies and offers insights into how these varied PPI regulatory modalities are relevant to customized drug discovery, with a focus on cancer.